2012
DOI: 10.4236/ijohns.2012.13022
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Central and Lateral Neck Dissection in Differentiated Thyroid Carcinoma

Abstract: Objective: To determine the histopathological correlation between central and lateral neck metastasis in differentiated thyroid carcinoma, and its potential therapeutic impact. Although the central neck dissection (CND) is recommended in differentiated thyroid carcinoma, the indication for lateral neck dissection (LND) remains controversial. Design: Retrospective study. Methods and Main Outcome Measures: Pathological analysis of systematic ipsilateral central neck dissection (CND) and LND performed with total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Metastatic LNs can be found in jugulo-carotid regions' level III or IV in approximately 70% of patients with PTC [15,16,32]. Mazzaschi et al [33] report high prevalence of positive lateral LNs in patients with positive central LNs, and low prevalence of "skip" metastases in negative central LNs. This suggests that lateral neck dissection may be unnecessary in patients with negative level VI LNs, unless lateral compartment metastases are clinically or US verified.…”
Section: Resultsmentioning
confidence: 99%
“…Metastatic LNs can be found in jugulo-carotid regions' level III or IV in approximately 70% of patients with PTC [15,16,32]. Mazzaschi et al [33] report high prevalence of positive lateral LNs in patients with positive central LNs, and low prevalence of "skip" metastases in negative central LNs. This suggests that lateral neck dissection may be unnecessary in patients with negative level VI LNs, unless lateral compartment metastases are clinically or US verified.…”
Section: Resultsmentioning
confidence: 99%
“…CNNs are the first nodes to harbor metastatic PTC, and the number of CNNMs is correlated with high recurrence risk and lower overall survival [ 4 , 28 ]. In PTC patients, the paratracheal and pretracheal lymph nodes are the most common subsites in the central compartment to harbor metastasis [ 6 , 17 , 29 ]. Our data showed that DLN-positive patients had significantly higher rates of paratracheal LNM (81.0% vs 31.1%, P < 0.001) and were 5.6 times more likely to harbor paratracheal LNM than DLN-negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…Fraser et al reported that 41 of 137 PTC patients (30%) had occult disease in just level III [ 13 ]. Moreover, Mazzaschi et al found that 32 of 40 patients (80%) with differentiated thyroid cancer who did not have preoperative evidence of cervical LNM had ipsilateral CNNM and LNNM simultaneously [ 29 ]. These studies highlight the great discrepancy between the high frequency of pathological LNNM and low rate of clinical lateral nodal involvement.…”
Section: Discussionmentioning
confidence: 99%